The new encyclopedia of Judaism - Wigoder, Geoffrey, 1922-1999.; Skolnik, Fred.; Himelstein, Shmuel (New York : New York University Press, 2002)
The new encyclopedia of Judaism is a comprehensive one-volume encyclopedia that presents every aspect of the Jewish religion and represents current thinking among scholars in the Reform, Conservative, and Orthodox movements. This revised and expanded edition updates the original thousand entries and adds nearly 250 new ones. Magnificently illustrated, it also contains a new introduction, a guide for usage, new illustrations, as well as a new annotated bibliography. There are biographical entries on biblical figures, rabbis, and others whose thoughts and actions have influenced the development of Judaism. Also included are dozens of insightful commentaries on specific prayers. Issues of particular contemporary interest are given special attention, as are women's roles, with a separate entry on the feminist movement and new biographical entries on figures ranging from Miriam and Deborah to Blu Greenberg and Suzannah Heschel. Particularly emphasized are the customs and folk traditions of Jewish outposts the world over. Authoritative and accessible, The new encyclopedia of Judaism serves as a standard one-volume Jewish reference work for the new millennium.
Updated ed. of: The encyclopedia of Judaism.
Includes bibliographical references (p. [828]-835) and index.
Keywords: Judaism -- Dictionaries